The Effect of Variation of Latex Mixed Storage Time Polystyrene and Natural Rubber Concentrate Latex on the Stability of the Emulsion by Using Emulsifier Sodium Lauryl Sulfate - Osman, Hakimah (Journal of Chemical Natural Resources, 2022)
Preparation of latex polystyrene with emulsifier ammonium lauryl sulfate (ALS) has been carried out by dissolving styrofoam (foam polystyrene) in toluene (30/70). And then polystyrene solution was mixed with aquadest, at ratios polystyrene and aquadest (v/v) were 90:10, 70:30, 50:50, 70:30, and 10:90 then added 10 mL of sodium lauryl sulfate (NLS) solution at concentrations 30%. The characterizations of the latex polystyrene included the stability determination during storage by density measurement and the determination of particle sizes and forms by microscopic optic observation. The results show that latex polystyrene ratio 90:10 is the most stable with density value constant during storage, are 0,848 g/mL for 30%. The particle sizes average is 1,56 mm with the distribution particle sizes decreasing as latex is 8,3 mm. Photomicrograph microscope optic shows that latex polystyrene NLS 30% has familiar particle forms and sizes